Uncoupling healthspan and lifespan in long lived Daf-2, Pmk-3 and Sgk-1 knockdown Caenorhabditis elegans - Siti Bazilah Zulkefli,; Geetha Gunasekaran,; Goon Jo Aan, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Modulation of genes expression in signaling pathways promotes longevity in Caenorhabditis elegans (C. elegans) but it is unclear whether this will improve healthspan. This study aimed to determine the healthspan of daf-2, pmk-3 and sgk-1 knocked-down worms. Health measures were determined at day 5, day 10 and day 15 of adult worms which were cultured in nematode growth media containing Escherichia coli. Heat resistance was determined by analysing the survival of worms at 37°C. Oxidative stress resistance was measured after exposure to 10mM hydrogen peroxide to analyse its survival capacity. Movement capacity was analysed by computing the distance travelled on solid media and the number of thrashing in liquid media. Results showed that the gene knockdown worms survived longer than wildtype worms. Daf-2 and pmk-3 knockdown increased movement capacity at day 5 and 10 in solid and liquid media but resulted in similar capacities to wildtype worms at day 15. Sgk-1 knockdown increased movement capacity only at day 5 in both media. The ability of gene knocked-down worms to withstand heat and oxidative stress significantly increased. In conclusion, knockdown of daf-2, pmk-3 and sgk-1 improved resistance to heat and oxidative stress but did not modulate movement incompetency at advanced ages C. elegans.